Integrating Islamic Values into Mathematics Education in Madrasah Ibtidaiyah - Rora Rizki Wandini (International Journal of Education, Language, and Social Science, 2026)
The integration of Islamic values into mathematics education in Madrasah Ibtidaiyah has emerged as an important pedagogical approach for simultaneously enhancing students' mathematical competencies and fostering their religious character. This study aims to examine the forms of Islamic values integration, the instructional strategies employed in mathematics education, and their implications for character development and the quality of mathematics learning. A Systematic Literature Review (SLR) was conducted by analyzing eight relevant peer-reviewed studies published between 2024 and 2025. The data were analyzed through a systematic process of study identification, thematic categorization, and evidence synthesis. The findings indicate that Islamic values are integrated into mathematics education by contextualizing mathematical concepts within Islamic teachings, developing Islamic-oriented instructional materials, and implementing contextual learning approaches. Such integration contributes to more meaningful learning experiences, increased learning motivation, improved conceptual understanding, and the development of students' religious character, particularly honesty, discipline, and responsibility. The review also reveals that empirical evidence regarding the effectiveness of Islamic value-integrated mathematics instructional models remains limited, highlighting the need for further classroom-based research to validate their educational impact